In-vitro antimicrobial activity of lemon bark extract against Salmonella shigella and Escherichia coli (Sciences of Phytochemistry, 2023)
The main objective of the study was the extraction and testing of the antimicrobial activity of the Lemon bark extract against the microorganisms involved in air and waterborne infections. The antibiotics are not very effective in the present day as the microorganisms are becoming resistant, the study concentrates on the antimicrobial activity and time ahead of the prophylactic potential of the lemon bark extract. Phytochemical analysis for the constituents of Lemon bark showed the presence of saponins, flavonoids and tannins in the aqueous form of solution. The potency test on microorganisms proved to be active against Salmonella shigella with the minimum inhibitory concentration of 100 mg/L was 16.27 mm, 150 mg/L was 16.43 mm and 250 mg/L was 16.73 mm. Meanwhile, for Escherichia coli for 100 mg/L was 13.20 mm, 100 mg/L was 13.10 mm and 150 mg/L was 13.13 mm.